2022
DOI: 10.3390/separations9070162
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach for Separating Essential Oil and Polysaccharides Simultaneously from Fresh Leaves of Guajava by Microwave-Mediated Hydrodistillation with Lithium Salts and Antibacterial Activity of Essential Oil

Abstract: The essential oils and polysaccharides from guava leaves have important functions. In the process of microwave extraction of plant essential oils and polysaccharides, pretreatment with lithium salts solution is helpful to increase the extraction rate. The experiment was conducted using a single factor method. Results were optimized by principal component analysis and response surface optimization. The optimal conditions were: LiCl dosage 45 μmol, microwave time 40 min, liquid-solid ratio 10, homogenization tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Furthermore, the C.V. is 5.37 %. The fitted regression equation conforms with the test principle and has high adaptability, as evidenced by the precise precision of 27.60 [ 35 ]. Through the fitting equation, we may further extract the outcomes of the experimental optimization.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the C.V. is 5.37 %. The fitted regression equation conforms with the test principle and has high adaptability, as evidenced by the precise precision of 27.60 [ 35 ]. Through the fitting equation, we may further extract the outcomes of the experimental optimization.…”
Section: Resultsmentioning
confidence: 82%
“…Response surface technique BBD was used to optimize the extraction parameters based on a single factor experiment in order to achieve the optimal ultrasonic-assisted extraction conditions, and the subsequent impacts and interactions of these variables on the yield were investigated [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 ). When using clearance as a variable, PC 1 (91.3 %) and PC 2 (6.1 %) were able to account for 97.4 % of the total variance that was kept in the model, nearly all the data [25] . Principal component analysis revealed that VC contributed the most to free radical scavenging, had a significant impact on antioxidant activity, and both had high ABTS clearance and DPPH clearance, so they were chosen as positive controls.…”
Section: Resultsmentioning
confidence: 99%